2005
DOI: 10.1038/sj.gt.3302454
|View full text |Cite
|
Sign up to set email alerts
|

Implications of cell cycle progression on functional sequence correction by short single-stranded DNA oligonucleotides

Abstract: Oligonucleotide-based sequence alteration in living cells is a substantial methodological challenge in gene therapy. Here, we demonstrate that using corrective single-stranded oligonucleotides (ssODN), high and reproducible sequence correction rates can be obtained. CHO cell lines with chromosomally integrated multiple copy EGFP reporter genes routinely show rates of 4.5% targeted sequence correction after transfection with ssODN. We demonstrate that the cell cycle influences the rates of targeted sequence cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
106
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(129 citation statements)
references
References 25 publications
21
106
2
Order By: Relevance
“…19 Over the past few years, it has become evident that DNA replication is the predominant cellular process underlying ssODN-mediated gene targeting in bacteria, [20][21][22] yeast 23,24 and various mammalian cell lines including ESCs. 16,25,26 According to this model, the ssODN anneals to its chromosomal complement when this becomes exposed as singlestranded DNA within the context of a replication fork. Upon annealing, the ssODN can serve as a primer for DNA synthesis to form a 'pseudo' Okazaki fragment, resulting in physical incorporation of the ssODN into the nascent DNA strand.…”
Section: Mechanistic Models For Ssodn-mediated Gene Targetingmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Over the past few years, it has become evident that DNA replication is the predominant cellular process underlying ssODN-mediated gene targeting in bacteria, [20][21][22] yeast 23,24 and various mammalian cell lines including ESCs. 16,25,26 According to this model, the ssODN anneals to its chromosomal complement when this becomes exposed as singlestranded DNA within the context of a replication fork. Upon annealing, the ssODN can serve as a primer for DNA synthesis to form a 'pseudo' Okazaki fragment, resulting in physical incorporation of the ssODN into the nascent DNA strand.…”
Section: Mechanistic Models For Ssodn-mediated Gene Targetingmentioning
confidence: 99%
“…Increasing the number of cells that progressed through S phase or slowing down replication fork progression during ssODN exposure resulted in elevated targeting frequencies in various mammalian cell lines. [25][26][27] The discontinuous nature of lagging strand DNA synthesis may expose more ssDNA regions and thus facilitate ssODN annealing. Indeed, studies in E. coli demonstrated that ssODNs corresponding in sequence to the lagging strand consistently performed better, irrespective of the direction of transcription, thereby establishing a direct link between ssODN polarity and the direction of replication through the target locus.…”
Section: Mechanistic Models For Ssodn-mediated Gene Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…3,9,10 Also in mammalian cells, a modestly increased efficiency of lagging strand over leading strand oligonucleotides was observed and the efficacy of oligonucleotide-mediated gene modification was dependent on the phase of the cell cycle, the highest frequencies being found when oligonucleotides were delivered to cells immediately after release of a G 1 /S block. 11,12 Furthermore, the efficacy could be improved by slowing down progression of replication forks again suggesting that also in mammalian cells at least one mechanism of oligonucleotide-mediated gene modification involves replication of DNA. 13,14 We have previously identified another parameter affecting the frequency of oligonucleotide-mediated gene modification: DNA mismatch repair (MMR).…”
Section: Introductionmentioning
confidence: 99%
“…34,35 It is interesting to note that not all corrected cells were able to survive and in fact, the only one-third of EGFP + sorted cell produced viable clones. Recently, Olsen et al 49 found that the majority of corrected CHO-K1 cells were arrested at G 2 /M stage and only 2% of the initially EGFPcorrected cells made viable colonies. The authors concluded that targeted sequence alteration by ODN by itself is somehow arresting mitosis of the corrected cells, suggesting difficulties in expansion of corrected cells.…”
Section: Discussionmentioning
confidence: 99%